2019
DOI: 10.1063/1.5090036
|View full text |Cite
|
Sign up to set email alerts
|

Very large remanent polarization in ferroelectric Hf1-xZrxO2 grown on Ge substrates by plasma assisted atomic oxygen deposition

Abstract: Plasma assisted atomic oxygen deposition was used to grow polycrystalline ferroelectric Hf1-xZrxO2 (x = 0.5–0.7) on technologically important (100) Germanium substrates showing sharp crystalline interfaces free of interfacial amorphous layers and strong evidence for the presence of a predominately orthorhombic phase. The electrical properties, evaluated using metal-ferroelectric-semiconductor (MFS) capacitors, show symmetric and robust ferroelectric hysteresis with weak or no wake-up effects. The MFS capacitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 26 publications
5
36
0
Order By: Relevance
“…[30,38,39]. This phase has been observed (and sometimes assumed) in polycrystalline ferroelectric layers grown via atomic layer deposition (ALD) [1,10,40,41], chemical solution deposition (CSD) [42], RF sputtering [43,44], co-evaporation and plasma assisted atomic oxygen deposition [40], as well as epitaxial layers obtained via pulsed laser deposition (PLD) [25,[33][34][35]37,45,46]. Recently, a higher energy polar rhombohedral (r-) phase has been observed on Hf 0.5 Zr 0.5 O 2 (HZO) layers epitaxially grown on SrTiO 3 (STO) substrates buffered with La 0.7 Sr 0.3 MnO 3 (LSMO) as the back-electrode [30].…”
Section: Introductionmentioning
confidence: 99%
“…[30,38,39]. This phase has been observed (and sometimes assumed) in polycrystalline ferroelectric layers grown via atomic layer deposition (ALD) [1,10,40,41], chemical solution deposition (CSD) [42], RF sputtering [43,44], co-evaporation and plasma assisted atomic oxygen deposition [40], as well as epitaxial layers obtained via pulsed laser deposition (PLD) [25,[33][34][35]37,45,46]. Recently, a higher energy polar rhombohedral (r-) phase has been observed on Hf 0.5 Zr 0.5 O 2 (HZO) layers epitaxially grown on SrTiO 3 (STO) substrates buffered with La 0.7 Sr 0.3 MnO 3 (LSMO) as the back-electrode [30].…”
Section: Introductionmentioning
confidence: 99%
“…Such distinguishing characteristics 2 lead to an upsurge in application-oriented research as well as in curiosity-driven fundamental research to solve questions such as why these materials are capable of sustaining the unconventional ferroelectricity 13-32 , how these materials negate the effects of depolarization fields 33,34 , and whether such a new type of ferroelectricity can be replicated in other simple oxide systems.A prominent feature of hafnia-based materials is polymorphism 35 . While the ground state in the bulk HfO2 is a non-polar monoclinic (m-, P21/c) phase, a plethora of low-volume both polar and non-polar metastable states can be stabilized at ambient conditions via a combination of strategies such as cationic and anionic doping 1,[25][26][27]29,32 , thermal and inhomogeneous stresses 36,37 , nanostructuring 38 , epitaxial strain 16,20,22,23,26,29,[39][40][41][42] , and oxygen vacancy engineering 43,44 , all of which can be suitably engineered into thin-film geometries.Based on first-principles calculations 15,39,[45][46][47] at least five polar polymorphs (with space groups Pca21, Cc, Pmn21, R3 and R3m) can be identified as those that can be experimentally obtained.Owing to its relatively low energy, the orthorhombic (o-) Pca21 phase is widely observed in hafnia-based films grown via atomic layer deposition (ALD) 1,17,24,25 , chemical solution deposition (CSD) 28 , RF sputtering on Si 18,21 and pulsed-laser deposition (PLD) on selected substrates 19,23,26,31,[40][41][42] . A slightly higher energy rhombohedral (r-) phase (R3m or R3) has been recently observed on epitaxial Hf1/2Zr1/2O2 films grown on SrTiO3 (STO) 39 .…”
mentioning
confidence: 99%
“…Ge substrate was annealed at 500 °C for 30 min, in vacuum, to obtain a clean surface, without C or O contamination. The HZO layer was deposited using plasma‐assisted atomic oxygen deposition (PA–AOD, see also the study by Zacharaki et al [ 9 ] ) method. Hf and Zr atoms were evaporated from metallic targets using two electron guns, in the presence O atoms generated by a remote radiofrequency plasma source, at an O 2 partial pressure of 6 × 10 −6 Torr and a substrate temperature of 225 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Hf 0.5 Zr 0.5 O 2 (HZO) layers with very good ferroelectric properties were successfully grown on p‐type Ge substrates. [ 9 ] It was also found that the shape of the capacitance–voltage ( C – V ) characteristic changes from metal–ferroelectric–semiconductor (MFS) like to metal–ferroelectric–metal (MFM) like while the temperature is increased from liquid nitrogen to room temperature (RT). [ 10 ] This behavior is accompanied by a significant shift of the positive coercive voltage, whereas the negative one remains nearly unchanged with decreasing temperature.…”
Section: Introductionmentioning
confidence: 99%